TOBACCO: THE REALITY AMONG GRADUATES IN THE HEALTH AREA (Fiep Bulletin - online, 2013)
The consumption of cigarette is responsible for the death of approximately 5 million of people each year. In this perspective, there are individual of several professional areas, mainly of the health area, that are responsible for informing about the damages and risks of cigarette consumption over the organism at a long term. However, despite of the current amount of knowledge about damage, some individuals still begin to smoke. The goal of the study is to show the reality of tobacco consumption among the students of the courses of Nursing, Nutrition and Physical Education of the UNIDERP of city of Campo Grande – MS. This research is characterized by a descriptive field study with a quantitative approach. The sample was composed of 418 students: smoking, occasionally smoking, ex-smoking and no-smoking, with an age average of 23,4 ± 13,8 years. The instrument of research used consisted of a questionnaire of 19 closed questions relative to the personal characteristics. Among all of the courses considered in this study, it was observed a prevalence of female genre about males in relation to total number of smokers and occasionally smokers. Among the population of 418 students, a total of 15% were individuals smoking, 85% no-smoking and 3,12% were ex-smoking. Data showed that in spite of the knowledge of cigarette damages, the students in the health area have still been continuing in this area, and it does not give a good example for population.
Keywords: Smoking; health; prevalence of smoking